2018
DOI: 10.12659/msm.909864
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of C-X-C Motif Chemokine 10 (CXCL10) Protects Mice from Cigarette Smoke-Induced Chronic Obstructive Pulmonary Disease

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a type of obstructive lung disease characterized by long-term breathing problems and poor airflow. COPD can progress to persistent decline of pulmonary function. This study explored the effect of CXCL10 on COPD induced by cigarette smoke (CS) and its underlying mechanism.Material/MethodsWild-type (WT) mice were randomly assigned into 3 groups: the control group, the CS group, and the intervention group. Mice in the CS group were exposed to CS and mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…CXCL10 and CXCL9 are chemokines produced in response to CS. They bind to receptors that are mainly expressed on T lymphocytes, powerfully attracting other cells from the innate and adaptive immunity 51–54. CCL11 attracts eosinophils that are important for the development of lung airway hyper-responsiveness in asthma and allergies 55.…”
Section: Resultsmentioning
confidence: 99%
“…CXCL10 and CXCL9 are chemokines produced in response to CS. They bind to receptors that are mainly expressed on T lymphocytes, powerfully attracting other cells from the innate and adaptive immunity 51–54. CCL11 attracts eosinophils that are important for the development of lung airway hyper-responsiveness in asthma and allergies 55.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed that IL-10 level was decreased in COPD patients while healthy volunteers expressed higher level of IL-10 [ 36 ]. Therefore, lung function and inflammation can be improved by decreasing inflammatory factors [ 37 ]. Tregs were differentiated for ameliorating inflammatory effect through TGF- β 1 in COPD against the Th17 proinflammatory effect, preserving inflammation balance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting CXCL10 seems an interesting option. An in vitro study has shown that CXCL10-neutralizing antibody can inhibit CSE-induced cell necrosis and activation of inflammatory cytokines in the 16HBE cell line [79]. In the same study, mice treated with CXCL10 neutralizing antibody did not develop COPD features (weight loss; reduction of lung function, increased levels of IL-6, and CCL2 in BALF and lung homogenate) as compared to cigarette smoke-exposed mice.…”
Section: Chemokines In Copd: Therapeutic Implicationsmentioning
confidence: 94%